The Impact of HBO1 in Ovarian Cancer - Marcos Quintela Vazquez (2018)
New approaches to improve current detection and treatment of ovarian cancer (OC), now the fifth leading cause of cancer death among women in the United Kingdom, are increasingly needed. Current cytotoxic chemotherapy and targeted therapies have failed to significantly impact overall patient survival and drugs targeting epigenetic readers, writers and erasers are receiving much attention as potential sources of novel OC therapies. The identification of target molecules and/or epigenetic regulators with key roles in the OC phenotype and progression could facilitate the development of new effective treatment strategies. The main purpose of this study was to assess the role of the ‘histone acetyltransferase binding to ORC-1’ (HBO1), an epigenetic regulator that plays important roles in diverse molecular processes including DNA replication and transcription. Previous studies found HBO1 overexpressed in OC tissues and, although the molecular basis of its role is still unclear, it may represent a novel target involved in the modulation of the OC phenotype. To better understand the roles of HBO1 in OC, we first profiled its expression in cellular models and found it to be overexpressed compared to a non-cancerous cell model. Further analysis of the HBO1 downstream regulatory pathways through the use of two different silencing methodologies confirmed that HBO1 is involved in the regulation of important cancer associated pathways and processes, as well as individual oncogenes and tumour suppressor genes. Analysis of the biomechanical properties of OC cells using Atomic Force Microscopy outlined a role for HBO1 in the establishment of an aggressive cancerous phenotype, as the membranes of HBO1-overexpressing cells were significantly more elastic than their HBO1-depleted counterparts. Overall, the results of this study suggest dynamic roles for HBO1, which ought to be studied further to determine whether this molecule could be considered an attractive target for the future development of OC therapies.